2023
DOI: 10.1186/s12954-023-00732-x
|View full text |Cite
|
Sign up to set email alerts
|

Remote harm reduction services are key solutions to reduce the impact of COVID-19-like crises on people who use drugs: evidence from two independent structures in France and in the USA

Abstract: Background Harm Reduction (HR) policies for People Who Use Drugs (PWUD) have a significant positive impact on their health. Such approaches limit the spread of infections and reduce opioid overdose mortality. These policies have led to the opening of specialized structures located mainly in big cities and urbanized zones. The COVID-19 pandemic reduced access to HR structures in locations undergoing lockdown. Before the pandemic, HR services in France and in the USA were complemented by the deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…First, given our OBAT operates as a hybrid telehealth model, we were unable to systematically distribute kits to patients receiving care primarily via telemedicine during the pilot period. Future iterations of this program may explore and incorporate strategies to provide tele-harm reduction services, which have been described in some studies [ 36 , 37 ]. Secondly, procurement of supplies and maintenance of kit inventory was difficult due to heterogeneity of vendors and pricing of kit supplies, unforeseen supply chain shortages, and unexpected variations in patient demands for specific kits.…”
Section: Discussionmentioning
confidence: 99%
“…First, given our OBAT operates as a hybrid telehealth model, we were unable to systematically distribute kits to patients receiving care primarily via telemedicine during the pilot period. Future iterations of this program may explore and incorporate strategies to provide tele-harm reduction services, which have been described in some studies [ 36 , 37 ]. Secondly, procurement of supplies and maintenance of kit inventory was difficult due to heterogeneity of vendors and pricing of kit supplies, unforeseen supply chain shortages, and unexpected variations in patient demands for specific kits.…”
Section: Discussionmentioning
confidence: 99%
“…Participants described issues related to the site's location and operational hours, and suggested that due to its current location, the site is not reaching its full potential. Evidence suggests that travel acts as a significant barrier for PWUD in accessing health and social services [23,24], and previous research has emphasized the importance of location and ensuring that travel or distance does not influence one's ability or decision to use at the site [25][26][27][28]. Studies have documented that when harm reduction sites are located far away from where PWUD commonly congregate or are in inconvenient locations, this can act as a significant deterrent for individuals to access the site, which subsequently results in low uptake [24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, while SSPs have long been champions for community-based naloxone distribution (the medication that reverses opioid overdoses), some now accelerate these efforts through strategies like vending machines and mail programmes. 9 , 10 Fentanyl test strips (FTS) are an emerging strategy used by SSPs; given the proliferation of fentanyl (a synthetic opioid 50 to 100 times more powerful than heroin) in heroin, but especially throughout the illicit drug supply including stimulants and counterfeit pills, paper test strips and other drug checking have emerged as a potential overdose mortality prevention strategy. 11 Drug checking can include testing for the type and quantity of substances; but, more often, and especially given the ability to use federal funding, it includes the distribution of FTS which are small strips of paper that detect the presence of fentanyl with similar strips developed for xylazine.…”
Section: Introductionmentioning
confidence: 99%